Evolution of the degree of co-polarization in high-birefringence fibers - Muga, Nelson J.
An analytical model accurately describing the evolution of the relative state of polarization between two signals in high-birefringence fibers is presented. The degree of co-polarization is calculated as a function of the angle between the principal axes of the fiber and the state of polarization of the two input signals, for two different input polarization schemes. It is shown that for small fiber lengths or narrow wavelength separation, launching the two signals with orthogonal polarizations can present a higher degree of co-polarization along the propagation: for large wavelength separation or long distances, the degree of co-polarization for the parallel scheme is always equal or higher than for the orthogonal case. The model for the degree of co-polarization is compared with theoretical and experimental four-wave mixing results in a dispersion shifted high-birefringence fiber. (C) 2010 Elsevier B.V. All rights reserved.